(untitled) (London Journal of Medical and Health Research, 2024)
Objective: The aim of our study was to assess the level of cytotoxicity of orthodontic appliances by checking the hypothesis that they induce an oxidative stress in mucosal cells. Methods: Our study included two groups: 29 controls and 34 patients undergoing orthodontic treatment with fixed appliances. Samples were collected before bonding (T0), after one month (T1), and after three months (T2) of treatment. Results: Results indicate the presence of oxidative stress following bonding, with significant differences in catalase activity (p = 0.039 at T1; p = 0.01 at T2) and in SOD activity (p = 0.001 at T1 and T2). The highest levels of enzymatic activities were recorded at T1 for both enzymesbut subsided at T2, suggesting cellular self-repair capabilities in response to orthodontic alloys. Conclusion: In view of our results, an appropriate choice of orthodontic alloys is required. Moreover, an identification of the subjects at risk for developing corrosion and galvanism and more attention are required to avoid ionic release in the oral cavity.